Methodology for Improving Mathematical Model of Ultrasonic Flowmeter to Study Its Error at Distorted Flow Structure - Fedir Matiko; Vitalii Roman; Roman Baitsar (Energy Engineering and Control Systems)
The paper presents a methodology for improving mathematical model of ultrasonic flowmeter (USM) results through the application of CFD simulation along with experimental reference data on measured consumption. On the basis of the proposed methodology, USM errors research method in terms of distortion of the flow structure has been developed. Using the proposed methodology mathematical model of two-path chordal USM has been improved and its study in terms of distortion of the flow structure after seven types of fittings has been conducted. According to the research results, concrete recommendations on the location of the USM towards the considered fittings have been proposed. The proposed recommendations will improve the accuracy of flow measurement by two-path USM by eliminating additional error due to the presence of distortions in flow structure. Testing of the proposed technique proves its correctness and application for any type of USM and various types of fittings.